Hypothalamic-pituitary axis dysfunction in critically ill patients with a low free thyroxine index - Mechanick, Jeffrey I.; Sacks, H. S.; Cobin, R. H. (Journal of endocrinological investigation, 1997)
The purpose of this study is to investigate the association of hypothalamic-pituitary axis abnormalities with the free thyroxine index (FTI) in critically ill patients. Fourteen critically ill patients and twenty healthy volunteers were studied using combined anterior pituitary gland testing with CRF, GHRH, TRH, and GnRH. The subjects were grouped as follows: I-healthy volunteers; II-sick/normal FTI; and III-sick/low FTI. Serial measurements of hormones were performed over a two-hour interval and the following parameters were measured: baseline level, response amplitude and time to maximal response. Response velocities and area-under-the-curves (integrated responses) were also computed. Group III had a longer mean ICU duration prior to testing than group II. Urinary cortisol, serum cortisol and serum PRL levels were elevated in groups II and III. However, group III had lower baseline ACTH levels, slower ACTH and TSH response velocities and decreased PRL integrated responses. Cortisol response parameters were similar between groups II and III. There were no differences in LH, FSH or GH response velocities or integrated responses among the 3 groups. These data confirm that critically ill patients develop hyperprolactinemia and hypothalamic-pituitary-adrenal axis activation but when a low FTI exists, a plurality of changes occur reflected by attenuated PRL, TSH and ACTH responses despite unaffected adrenal cortisol output.